Aplikasi Grafologi dari Huruf “t” Menggunakan Jaringan Syaraf Tiruan - Iwan Awaludin; Aulia Khairunisa (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Graphology is a branch of science which classifies human personality from handwriting. Graphologists observe the patterns of handwriting and compare it with personality class database. Computers can be trained to do the same procedure of human personality classification based on handwriting. The procedure is to perform digital image processing that extracts features from handwriting images. The features will become input for Artificial Neural Network. Neural networks that are already configured with a number of hidden layers, the number of neurons, activation function, and the particular learning algorithm will be able to recognize certain classes of human handwriting, thus his personality. Tested configurations include: changing the number of neurons in the hidden layer of eight to twelve, binary image resizing, changing the activation function, and also changing the learning algorithm. Results of simulation and analysis are also provided.